Antifungal activity of extracts from three species of lichens in Cuba. - Vaillant-Flores, Daymara Idonay; Gómez-Peralta, Marlene; Romeu-Carballo, Carlos Rafael; Ramírez-Ochoa, Rebeca; Porras-González, Angela (Agronomía Mesoamericana, 2015)
The objective of this work was to evaluate the antifungal activity of the three lichens extracts. Extracts from Leptogium cyanescens, Physcia americana and Pyxine aff. cocoes were collected from the lichens thallus in 2009 in areas fromo the Cienfuegos Botanic Garden, Cuba. The fungicide activity was evaluated against phytopathogens fungi of potato: Rhizoctonia solani and Phytophthora nicotianae var parasitica. The study was conducted from 2009 to 2011. The compounds were extracted with acetone, concentrated by rotoevaporation, and evaluated at concentrations of 0,01 and 0,07% in potato dextrose agar (PDA) culture medium; stock solution was made of 5% dimethilsufoxide. These extracts were classified by their toxicity as: toxic, slight and moderately toxic and harmless. The extracts from P. americana of 0,07% inhibited P. nicotianae 100%, and it showed values over 50% for R. solani. L. cyanescens only showed fungicide activity in both phytopathogens at the maximum concentration studied; similar results were obtained with the extract from P. aff. cocoes. The lichens extracts were classified as lightly toxic at the maximum concentration, and harmless at the minimum concentration.